2019
DOI: 10.2166/ws.2019.016
|View full text |Cite
|
Sign up to set email alerts
|

Microbial risk assessment of drinking water filtration dispenser toll machines (DFTMs) in Mahasarakham province of Thailand

Abstract: This investigation aimed to assess the microbial quality of drinking water produced by drinking water filtration dispenser toll machines (DFTMs) to assess the health risk of DFTM water. A total of 210 samples were randomly collected of 70 DFTMs within a radial distance of 500 metres around Mahasarakham University. The prevalence of Escherichia coli and Staphylococcus aureus in the DFTM water was 54.17% and 16.67% with an average concentration of 1.04 log cfu/ml and 0.26 log cfu/ml, respectively. The risk calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Ten out of 60 samples tested for the presence of total coliform bacteria (16.67%) and five out of 60 samples tested for fecal coliform bacteria (8.33%) were found unsatisfactory concerning microbiological quality. E. coli could not be detected in any sample, a finding in accordance with similar studies recently conducted (Pratum & Khananthai 2017;Yongyod 2018;Wibuloutai et al 2019). The absence of these microorganisms, considered to represent an indicator of fecal contamination, renders water quality satisfactory and safe without health concerns.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Ten out of 60 samples tested for the presence of total coliform bacteria (16.67%) and five out of 60 samples tested for fecal coliform bacteria (8.33%) were found unsatisfactory concerning microbiological quality. E. coli could not be detected in any sample, a finding in accordance with similar studies recently conducted (Pratum & Khananthai 2017;Yongyod 2018;Wibuloutai et al 2019). The absence of these microorganisms, considered to represent an indicator of fecal contamination, renders water quality satisfactory and safe without health concerns.…”
Section: Discussionsupporting
confidence: 89%
“…However, previous investigations found that 76.6% of examined dispensers were contaminated with fecal coliform microbes, Escherichia coli, fecal streptococci, Pseudomonas aeruginosa or Staphylococcus spp. and revealed a prevalence of E. coli and S. aureus in filtration-treated dispenser water of 54.17% and 16.67%, respectively (da Silva et al 2008;Wibuloutai et al 2019). In particular, levels of E. coli and S. aureus are frequently monitored as indicators of the hygienic status of drinking water (Jessen et al 2013).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 16 23 ] The low level of E. coli in this study might show the low risk of illness from E. coli exposure as described in the previous quantitative microbial risk assessment (QMRA) of drinking water in Mahasarakham province of Thailand. [ 23 ] In addition, E. coli detected in drinking water can be implied that pathogenic bacteria, viruses, and parasites may also be contaminated.…”
Section: Discussionmentioning
confidence: 83%
“…Routine maintenance with effective sanitisation of all outer and inner surfaces is crucial [45] . We would like to highlight the stressing needs for proper sanitisation on the contact points between users and water vending machines for the persistent hygienic issues [46][47][48] .…”
Section: Bacterial Colonies On Hicrome Tm Coliform Agarsmentioning
confidence: 99%